1990
DOI: 10.1021/ic00326a024
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium constants for the binding of aluminum to human serum transferrin

Abstract: believe that the precise definition of the coordinate geometry of copper a t the active site will be crucial to understanding its functional operation. Also, the subtle changes t h a t allow t h e dinuclear site to become catalytically active in, for example, tyrosinase and laccase'1*42-44 will also be an interesting outcome of gaining a more precise definition of t h e active-site structure of hemocyanin a n d its related binuclear copper proteins.45 42)Karlin, K. D.; Gultneh, Y. Prog. Inorg. Chem. 1987, 35, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 5 publications
3
60
0
Order By: Relevance
“…The difference in binding constants, logKT-logK: = 1.3, is greater than would be the case if both lobes bound Sc3+ equally strongly (dlogK* = 0.6). Therefore, it can be concluded that one lobe has a higher affinity for Sc3+ than the other, as has been found for several other metallotransferrins [ 10,15,201.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The difference in binding constants, logKT-logK: = 1.3, is greater than would be the case if both lobes bound Sc3+ equally strongly (dlogK* = 0.6). Therefore, it can be concluded that one lobe has a higher affinity for Sc3+ than the other, as has been found for several other metallotransferrins [ 10,15,201.…”
supporting
confidence: 65%
“…In particular, tyrosinate side-chains are likely to play dominant roles since two of them bind to the metal and transferrin is the only known metalloprotein in which this is known to be the case. About 30 metal ions are known to bind to transferrin with either carbonate, oxalate or other carboxylates as synergistic anion [3], and the binding constants for 12 divalent and trivalent metal ions with carbonate as anion have previously been determined by ultraviolet difference spectroscopy [8,10,15,[22][23][24][25][26].…”
mentioning
confidence: 99%
“…Therefore, pM values were calculated for the Fe and Al complexes with the ligands under study and are depicted on Table 2, together with the corresponding values for a set of synthetic and biological ligands, namely, polyhydroxypyridinone-based ligands, such as hexadentate 3,2-HP (tripodal Tren(Me-3,2-HOPO) (Tren = tris(2-aminoethyl)amine, Me-3,2-HOPO = 1-methyl-3,2-hydroxypyridinone), [24] linear 3,4-LI(Me-3,2-HOPO) (3,4-LI = N 1 -(3-aminopropyl)butane-1,4-diamine), [25] a hexadentate tripodal 3,4-HP (CP254), [26] tetradentate 3,4-HP (IDAA C H T U N G T R E N N U N G (3,4-HP) 2 (IDA = iminodiacetic acid), [27] EDTAA C H T U N G T R E N N U N G (3,4-HP) 2 [12] ), and some well known non-hydroxypyridinone strong synthetic chelators such as N,N'-bis(2-hydroxybenzyl)ethylenediamine-N,N'-diacetic acid (HBED), [28] EDTA, [29] DTPA = diethylene triamine pentaacetic acid, [29] desferrioxamine (DFO), [30,31] DFP, [19] and the endogenous ligand, transferrin. [30,32] Analysis reveals that the herein developed hexadentate chelators are more potent than the others, except HBED, reported in Table 2 towards iron. Thus, the high metal chelating affinity revealed by these novel hexadentate hydroxypyridinones undoubtedly constitutes a strong motivating factor for pursuing biodistribution studies with both ligands to evaluate their removal capacity towards hard metal ions.…”
Section: Esi-ms Measurements Performed For Solutions Of Thementioning
confidence: 82%
“…In a number of publications absorption at 240 nm has been taken to reflect the formation of the AI Tf complex and as such this was used to monitor the binding of Study of Al-Tf bindin9 by IEF aluminum to transferrin (Trapp 1983, Cochran et al 1984, Harris & Sheldon 1990, McGregor et al 1990, Kubal et al 1992, Aramini et al 1993. Based on this assumption, maximal absorption at 240 nm was assumed to be correlated with full saturation.…”
Section: Loading Oj Transferrinmentioning
confidence: 99%
“…Like iron, in the circulation, aluminum is transported by transferrin, while albumin and citrate appear to play a minor role (van Ginkel et al 1990, Harris & Sheldon 1990. Competition between iron and aluminum for transferrin binding is suggested in view of the negative correlation between serum iron and serum aluminum in the dialysis population (Vanuytsel et al 1992, van Landeghem et al 1994.…”
Section: Introductionmentioning
confidence: 99%